2013
DOI: 10.3168/jds.2012-6438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant enzyme inactivation or sterilization on lipolysis and proteolysis in alfalfa silage

Abstract: This experiment studied the contribution of plant enzymes and microbial activity on lipolysis and proteolysis in ensiled alfalfa. Before ensiling, the wilted alfalfa was treated with plant enzyme inactivation by autoclaving or with sterilization by γ-ray irradiation. The treated alfalfa was then inoculated with commercial lactic acid bacteria inoculants and ensiled for 40 d. Alfalfa without treatment was ensiled as the control. The content of total fatty acid (FA) after ensiling decreased 43% in the control si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 34 publications
(52 reference statements)
6
35
0
1
Order By: Relevance
“…It is interesting to note that the ensiling process had little impact on the CP of MZ and HS (<5% change), but it reduced the CP concentration by 23% from 64 g CP per kg of DM in FS to 49 g CP per kg of DM in FSS. This may be related to the proteolysis reaction during ensiling of the forages (Heron et al 1989;Ding et al 2013). Merry et al (2006) observed more active proteolysis reaction when pH is higher in silage, due to low WSC and starch in forage before ensiling.…”
Section: Chemical Composition Of Forages and Silagesmentioning
confidence: 94%
“…It is interesting to note that the ensiling process had little impact on the CP of MZ and HS (<5% change), but it reduced the CP concentration by 23% from 64 g CP per kg of DM in FS to 49 g CP per kg of DM in FSS. This may be related to the proteolysis reaction during ensiling of the forages (Heron et al 1989;Ding et al 2013). Merry et al (2006) observed more active proteolysis reaction when pH is higher in silage, due to low WSC and starch in forage before ensiling.…”
Section: Chemical Composition Of Forages and Silagesmentioning
confidence: 94%
“…The pH was measured immediately; then, one part of the filtrate was acidulated with 7.14 M H 2 SO 4 and filtered with a 0.45-µm dialyzer. Lactic acid, acetic acid, propionic acid, and butyric acid were analyzed by HPLC (Shodex KC-811 column; Shimadzu, Kyoto, Japan; oven temperature: 50°C; flow rate: 1 mL/min; SPD-10Avp, Shimadzu: 210 nm) as described previously (Ding et al, 2013). A total of 1 mL of 250 g/L (wt/vol) trichloroacetic acid was added to 4 mL of the second part of the filtrate from each bag.…”
Section: Chemical and Fa Analysesmentioning
confidence: 99%
“…Following this, 1 g of NaHSO 4 was added and, after vortexing for a further 2 min, the samples were centrifuged at 1,400 × g for 5 min at 4°C. The upper liquid layer was used for the determination of FAME by GC with attached MS (model 6890N-5975C, Agilent Technologies, Santa Clara, CA) fitted with a fused-silica capillary column (30 m × 0.25 mm × 0.50 µm; DB-FFAP, Agilent) as described previously (Ding et al, 2013).…”
Section: Chemical and Fa Analysesmentioning
confidence: 99%
See 2 more Smart Citations